Comparison of plasma leptin and zinc levels in elite athletes and sedentary people - Arikan, Sukran; Akkus, Hasan; Halifeoglu, Ihsan; Baltaci, Abdulkerim Kasim (Wiley, 2008)
In consideration of leptin effects such as reducing food intake and increasing energy consumption, many researchers have sought to examine the relation between leptin and exercise. The presence of reports arguing that zinc, can be a mediator in leptin production indicates a possible relation between zinc and leptin. The present study aims to determine plasma leptin levels in elite weightlifters and examine their relation with zinc. The study enrolled 30 healthy volunteers in the 18-27 age range. The subjects were allocated to groups in equal numbers: Group 1, Control Group: the group included subjects who did not exercise regularly. Group 2, Elite Weightlifter Group: the group included elite weight lifters who were selected to the national team in their weight classes, who exercised regularly and whose values were measured during rest in the training period. Levels of plasma leptin and zinc were determined in the blood samples collected front the subjects included in the study. Comparison of serum leptin and zinc values between groups showed that leptin and zinc levels in the control group were significantly higher than those in the weightlifters; and that leptin levels decreased significantly in parallel with the low zinc levels. It can be concluded that physical activity brings about changes in leptin secretion, which in turn, can be significantly related with zinc (p < 0.01). Copyright (c) 2008 John Wiley & Sons, Ltd.
Keywords: elite weightlifters; leptin; zinc